Proceedings of the SIGCHI Conference on Human Factors in Computing Systems - CHI '92 1992
DOI: 10.1145/142750.142897
|View full text |Cite
|
Sign up to set email alerts
|

User centered development of a general practice medical workstation

Abstract: The goal of the PEN&PAD project is to design and develop a useful and usable medical workstation for day-to-day use in patient care. The project has adopted a user centred approach and direct observations of doctors, participative design and Formative Evaluation have therefore been an integral part of the process of software development. Indeed, doctors have been involved from the earliest stages of the project. The project has focussed on British General Practitioners, but the methods which have been evolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Evaluation workshop [60] or Workshop test [28] Usability AND "evaluation workshop" OR "workshop test"…”
Section: Selection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation workshop [60] or Workshop test [28] Usability AND "evaluation workshop" OR "workshop test"…”
Section: Selection and Analysismentioning
confidence: 99%
“…Rector et al [60], Obrist et al [56], and Wright and Monk [14] concluded that the direct access to users' reports served to strengthen the understanding in the design team of the users' needs. The remaining four studies concerning downstream impact, provided more detailed evidence on this.…”
Section: Which Levels Of Downstream Impact Are To Be Expected For Usementioning
confidence: 99%
“…Not only do the simple observations need to be represented, but also the complex layer of state-ments representing the decision making about those observations. In our experience in the PEN & PAD system [3,4], the number of meta statements relating basic observations in the medical record to problems, decisions, and the mechanics of clinical care -requests, responses to requests, etc.is typically several times greater than the number of statements recording direct observations. For example, to obtain anything like a complete model of care we must record not only that the patient had diabetes, had a glycosylated haemoglobin measurement of 7.5, and was prescribed diabinase, but also that the diabetes was part of the problem of diabetic care, and that the glycosylated haemoglobin and the prescription for diabinase related to the problem of diabetes, that the prescription was a repeat of the previous prescription and was an increase on the previous dosage, etc.…”
Section: The Complexity Of Medical Recordsmentioning
confidence: 99%
“…The claim that these would be rejected by doctors is irrelevant, for the need for manual intervention prevents the system validating or actively supporting data input by clinicians (or other clinical systems) [4], or the reliable exchange of information. The lack of constraints also limits consistency of structure; the semantics of the classification hierarchies are often heterogeneous and implicit, which severely limits the inferences that can be drawn.…”
Section: Introductionmentioning
confidence: 99%